Daylight driven design in enhancing energy efficiency of office building in tropical climate - Goh, Zheng Lin (2017)
The aim of this research is to establish a daylight driven office building design that improve the energy efficiency of office building in Malaysia. To achieve this aim, the key principles of daylighting are to be establish. The daylighting key principles are solar heat gain minimization, glare prevention, deep penetration of daylight, uniform daylight distribution, electrical light response to harvested daylight, interior planning and design consideration. The research methodology chosen are computer simulation and comparative analysis of case studies. Computer simulation is carried out to determine the optimum building form with minimal solar radiation and the effectiveness of light shelf to harvest daylight in relation to its width. While comparative analysis of case study is carried out to identify the daylighting strategies that implemented and its effectiveness. The results of the research can be categorise as three part that is comparative analysis of case studies, solar radiation simulation and daylighting simulation. Firstly, the three selected case studies show that consideration of all daylighting key principles is crucial to achieve high energy efficiency office building in Malaysia. Secondly, result of six cases of solar radiation simulations show that building form that has podium and tower with self-shading facades has less solar heat gain compared to other building form that do not have those characteristics. Lastly, the results of six cases for daylighting simulation shows that implementation of light shelf of 1500mm width enable to reduce glare effectively but slightly reduced desirable illuminance of 300-400 lux. Therefore, integrated approach that is introduction of reflective ceiling is required to increase the floor area with desirable illuminance of 300- 400 lux for healthy working environment.